Financial Management of the Grand Mosque in Aceh from the Perspectives of the Sharia Economic Law - Iqbal, Muhammad; Nurdin, Ridwan; Devy, Soraya; Surya, Jen; Yunanda, Rizki (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
This research was conducted in response to the phenomenon that many mosques in Aceh do not prepare financial reports in accordance with ISAK 35 (Interpretation of Financial Accounting Standards). Since 2019, the Financial Accounting Standards Board (DSAK) has replaced PSAK 45 and ratified ISAK 35 as the guideline for the presentation of financial statements of non-profit entities, which took effect in January 2020. This standard also applies to the financial reporting of mosques as non-profit institutions. At present, the accountability of mosque financial management in Aceh is generally limited to reports of cash receipts and disbursements, which constitute only a part of the cash flow statement. However, ISAK 35 stipulates that the financial statements of non-profit entities should consist of: (1) a Statement of Financial Position, (2) a Statement of Comprehensive Income, (3) a Statement of Changes in Net Assets, (4) a Statement of Cash Flows, and (5) Notes to the Financial Statements. Given the large number of mosques in Aceh and to avoid the time constraints of completing this research, this study focuses solely on the Grand Mosques managed by the regencies/cities in Aceh Province. The findings reveal that the financial reports of the Grand Mosques across the 23 regencies and cities in Aceh remain incomplete. First, the reports prepared and presented by mosque administrators are still limited to records of cash receipts and expenditures. Second, mosque management personnel generally lack sufficient knowledge of financial reporting practices and standards. Third, most mosque administrators and staff are elderly, which further constrains the implementation of proper financial reporting procedures. It is also important to emphasize that mosque financial management must be based on sharia-based financial and accounting principles so that the mosque is not only a center of worship but also an institution for economic, educational, and community empowerment